Preformed mRNA in Cotyledons of Ungerminated Seeds of Cicer arietinum L. - Matilla, Angel (1980)
Polyadenylated RNA was isolated from total RNA extracted from cotyledons of ungerminated or 18-hour-germinated chick-pea seeds by affinity chromatography on oligo(dT)-cellulose. Both poly(A)-containing RNA fractions exhibited a template activity when assayed in two cell-free translation systems, wheat germ extracts, and nuclease-treated reticulocyte lysates. Translation of preformed mRNA from cotyledons of dry seeds was completely abolished in the presence of several inhibitors of polypeptide chain initiation and also in the presence of the two “cap” analogues m(7) GTP and m(7) GMP. The patterns of polypeptides synthesized by translation of poly(A)-containing RNAs from cotyledons of ungerminated or 18-hour-germinated seeds, in the wheat germ system, analyzed by electrophoresis and autoradiography, were similar but not identical. It is concluded that cotyledons of dry Cicer arietinum L. seeds contain preformed mRNA.